(untitled) (Journal of Global Arts Studies, 2025)
Background: There are a wide variety of traditional Chinese Musical Instruments, which can be classified into wind instruments, stringed instruments, plucked instruments and percussion instruments according to different playing methods. In various folk activities held by the people nowadays, the use of Musical Instruments shows a unique distribution characteristic based on different occasions. Objective: The article takes the blessing ritual of Zhengyi Taoism in Cangnan County, Wenzhou City, Zhejiang Province as a case study, aiming to explore the use of timbre of the principal musical instruments in different ritual procedures and their functional significance. Methods: By integrating field investigations, descriptions of ritual music, in-depth interviews with musicians, and audio spectrum analysis, the patterns of instrument usage during rituals are recorded and analyzed. Results: It is further discovered that the Musical Instruments used in the rituals of the Zhengyi School of Taoism have been deeply embedded in the ritual structure and cultural context. Their functionality is reflected in the specific timbres of the instruments and the symbolic ritual process, which enhance the emotions of the field and strengthen the cultural identity of the insiders. Conclusion: Revealing the systematic and symbolic connotations of the timbres of the instruments in the ritual system.